Assessing cold plasma’s impact on banana growth and fusarium wilt control - Rajakumar, Priya; Akmal Baharum, Nadiya; Lutfi, Afiqah Insyirah; Mohd Sadali, Najiah; Mispan, Muhamad Shakirin; Kuang, Lim Lian; Ling, Yap Seong; Khalid, Norzulaani; Rejab, Nur Ardiyana (Korean Society of Plant Pathology, 2024)
Bananas (Musa spp.), which serve millions of people worldwide, face a serious threat from Fusarium wilt (FW) disease caused by Fusarium oxysporum f. sp. cubense (Foc). Developing disease-resistant varieties particularly through breeding is challenging due to banana’s seedless nature (parthenocarpic). As an alternative, cold plasma (CP) technology, has the potential to be used for crop improvement. Our study demonstrates a favourable impact of CP on the growth performance of banana (Berangan cultivar, AAA) in terms of height, leaf number and stem diameter. CP-treated plants also displayed delayed disease progression as well as lower disease severity indicated by slightly lower value of leaf symptoms index and rhizome discoloration index compared to the control plants. Additionally, quantitative real-time polymerase chain reaction analysis revealed differential expression of several defence (PR1, WRKY22, PAL, and CEBiP) and growth (Cytochrome P450, NAC68, and CAT) related genes in CP-treated plants, particularly in conjunction with Foc infection. These findings shed light on the potential use of CP in managing FW in banana and offer insights into possible mechanism behind improved traits.